Utility of Automated Hematology Analyzers in Diagnosis of Infective Etiologies: An Adjunct to Conventional Diagnostic Tools - Patel, Keyuri Bharat; Ranapurwala, Mustafa Fakaruddin; Mansuri, Neelofar Safilmohmad; Singh, Rohit Kumar; Patel, Anjali Nimeshkumar; Padharia, Dharti Pravinbhai (Annals of Pathology and Laboratory Medicine, 2021)
Background: Febrile illnesses such as malaria and dengue are challenging to differentiate clinically. For more than a century, the diagnostic approach is by clinical features and microscopy or manual immune-chromatographic tests. Automated cellular (WBC) indices from hematology analyzers may afford a preliminary rapid distinction. Several abnormal scattergrams during routine CBC analysis appear for the malaria and dengue. Material and Methods: The present study is an observational, prospective study undertaken to evaluate the diagnostic utility of Sysmex XN-L series hematology analyzer as a screening tool to trigger specific testing for malaria and dengue. It includes patients suffering from either of the two febrile illnesses (malaria or dengue) at Hematology and microbiology section of Central Diagnostic Laboratory of a tertiary care centre in Central Gujarat. The sensitivity, specificity, PPV and NPV was performed for each abnormal pattern noted on scattergram for malaria and/or dengue. Interobserver variation is also taken in consideration. Results: Malaria cases showed a significant statistical association with the presence of an extended neutrophil zone and dengue positive cases with NS1 antigen, IgG and IgM antibodies testing showed significant association with the hourglass pattern. Higher degree of agreement was noted for the hourglass pattern, doubling of neutrophil zone pattern among the observers Conclusion: Significant statistical correlation was observed for extended neutrophil zone and malaria cases, hourglass pattern and dengue cases with a good agreement among the observers.